Eight Years of Collaboration on Biosafety and Biosecurity Issues Between Kazakhstan and Germany as Part of the German Biosecurity Programme and the G7 Global Partnership Against the Spread of Weapons and Materials of Mass Destruction - Lukas Peintner; Edith Wagner; Edith Wagner; Anna Shin; Anna Shin; Nur Tukhanova; Nur Tukhanova; Nurkeldi Turebekov; Karlygash Abdiyeva; Olga Spaiser; Yelena Serebrennikova; Erik Tintrup; et al. (Frontiers Media S.A., 2021)
In 2013, the German Federal Foreign Office launched the German Biosecurity Programme with the aim to minimise risks associated with biological substances and pathogens. In this context, the German-Kazakh Network for Biosafety and Biosecurity was established in 2013 and constitutes a successful collaboration between Kazakh and German biomedical organisations, under the co-management of the Bundeswehr Institute of Microbiology (IMB), and the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH. Ever since then, a network of scientists, stake holders and policymakers has been established, aiming to work on highly pathogenic, potential biological warfare agents with the focus on biosafety and biosecurity, surveillance, detection and diagnostics, networking and awareness raising of these agents in Kazakhstan. Over the past 8 years, the project members trained four PhD candidates, organised over 30 workshops and trainings with more than 250 participants and conducted more than 5,000 PCR assays and 5,000 serological analyses for surveillance. A great success was the description of new endemic areas for Orthohantaviruses, the mixture of two Crimean-Congo haemorrhagic fever virus genetic clusters, new foci and genetic information on tick-borne encephalitis virus and rickettsiae in Kazakh oblasts. The latter even led to the description of two new genogroups. Furthermore, joint contributions to international conferences were made. In this report, we summarise the evolution of the German-Kazakh Network for Biosafety and Biosecurity and critically reflect on the strengths and possible weaknesses. We were able to establish a viable network of biosafety and biosecurity shareholders and to accomplish the aims of the German Biosecurity Programme to lower biosecurity risks by increased awareness, improved detection and diagnostic methods and surveillance. Further, we reflect on forthcoming aspects to lead this interstate endeavour into a sustainable future.